Lithium dendrite growth resistant composite diaphragm, preparation method thereof and lithium ion battery

By using a composite separator of metal nitrate-loaded mesoporous carbon material and ceramic powder in lithium-ion batteries, the problems of lithium dendrites growth and thermal shrinkage of the separator are solved, and the electrochemical and safety performance of the battery is improved.

CN119852641AActive Publication Date: 2025-04-18安徽得壹能源科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510042428.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-18
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

In the later stage of service, lithium-ion batteries have deteriorated circulation and safety performance due to lithium dendrites growth, out-of-control volume effects and ineffective lithium that cannot participate in circulation, which can easily cause internal short circuits, thermal runaway, battery rupture, fire and even explosion.

Method used

A composite separator composed of metal nitrate-loaded mesoporous carbon material and ceramic powder is adopted to inhibit the growth of lithium dendrites through the loading and sustained release mechanism of metal nitrates, and prevent the thermal shrinkage of the separator substrate at high temperatures.

Benefits of technology

Effectively inhibit the growth of lithium dendrites, prevent the separator substrate from heat shrinking at high temperatures, protect the negative electrode, improve the electrochemical and safety performance of the battery, and improve the cycle stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852641A_ABST
    Figure CN119852641A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium dendrite growth resistant composite diaphragm, a preparation method thereof and a lithium ion battery, and belongs to the technical field of lithium ion batteries. The preparation method comprises the following steps: preparing a metal nitrate loaded mesoporous carbon material, wherein the metal oxidation reduction potential of metal nitrate is higher than that of lithium; uniformly mixing the metal nitrate loaded mesoporous carbon material, ceramic powder, a binder, a dispersant, a surfactant and a thickener aqueous solution in water to prepare mixed slurry; and coating one side of the diaphragm base material with the mixed slurry, and drying to obtain the diaphragm. The lithium dendrite growth-resistant composite diaphragm provided by the invention can continuously inhibit the growth of lithium dendrites, and a negative electrode is jointly protected through the synergistic effect of all the substances so as to improve the electrochemical and safety performance of a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a composite diaphragm that resists lithium dendrite growth, a preparation method thereof, and a lithium ion battery. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Compared with traditional secondary batteries, lithium-ion batteries have the advantages of high energy density, environmental friendliness, and long service life. They are currently widely used in digital electronic products, new energy vehicles, and energy storage. With the development and application of lithium-ion batteries with high energy density, safety issues have become the focus of people's attention. In the later period of battery service, the rampant growth of lithium dendrites, uncontrolled volume effects, and invalid lithium that cannot participate in the cycle seriously restrict its cycle performance and safety performance. In many safety accidents, internal short circuit is the main cause of thermal runaway of lithium-ion batteries. Because the direct contact between the highly oxidizing cathode and the highly reducing anode causes a large amount of heat to be released instantly, the internal temperature will rise sharply, which will trigger a series of exothermic reactions. These reactions generate a large amount of heat and gas, causing a sudden increase in internal pressure and temperature, triggering thermal runaway, and ultimately causing battery rupture, fire, and even explosion.

[0004] The prior art usually uses modified diaphragm substrates to improve the puncture resistance of diaphragm lithium dendrites. For example, the patent with publication number CN114069156A discloses a puncture-resistant diaphragm and its application in lithium batteries, which improves the mechanical strength of the bacterial fiber membrane by using a modified bacterial cellulose membrane and a modified fiber layer for compounding. The patent with publication number CN115863915A discloses a heat-resistant shrinkage-resistant puncture-resistant polyolefin diaphragm material and a preparation method thereof, which is improved by using a mixed raw material composed of modified polyolefin, modified ethyl cellulose, high-density polyethylene, antioxidant, nucleating agent and dispersant. However, the above patents mainly enhance the puncture resistance of the substrate, and do not solve the growth and puncture problem of lithium dendrites. Summary of the invention

[0005] In view of this, the present invention provides a composite diaphragm that resists lithium dendrite growth, a preparation method thereof and a lithium-ion battery. The effective substance in the composite diaphragm has the characteristic of continuous release, which can sustainably inhibit the growth of lithium dendrites, and has the characteristic of inhibiting the thermal shrinkage of the diaphragm substrate at high temperatures, thereby protecting the negative electrode to improve the electrochemical and safety performance of the battery.

[0006] In a first aspect, the present invention provides a method for preparing a composite separator having resistance to lithium dendrite growth, comprising the following steps:

[0007] S1. preparing a metal nitrate-loaded mesoporous carbon material, wherein the metal nitrate has a metal redox potential higher than that of lithium;

[0008] S2, mixing the metal nitrate-loaded mesoporous carbon material, ceramic powder, binder, dispersant, surfactant and thickener aqueous solution in water to prepare a mixed slurry;

[0009] S3. Coat the mixed slurry on one side of the diaphragm substrate and dry it to obtain a composite diaphragm that resists lithium dendrite growth.

[0010] Preferably, the preparation method of the metal nitrate-loaded mesoporous carbon material is as follows: adding the mesoporous carbon material to a metal nitrate aqueous solution, heating and stirring, then cooling and recrystallizing, and filtering to obtain the material.

[0011] Furthermore, the mesoporous carbon material is selected from one or more of ordered mesoporous carbon CMK-3, nanoporous carbon NCP, porous activated carbon, porous carbon nanotubes, porous carbon fibers or porous carbon aerogels; the metal nitrate is selected from one or more of magnesium nitrate, calcium nitrate or potassium nitrate; the mass ratio of the mesoporous carbon material to the metal nitrate is 1:(1 to 5).

[0012] Furthermore, the temperature of the heating and stirring is 50-100° C., the speed of the heating and stirring is 500-1000 rpm, and the time of the heating and stirring is 10-60 min.

[0013] Preferably, in step S2, the mass ratio of the metal nitrate-loaded mesoporous carbon material, ceramic powder, binder, dispersant, surfactant, thickener aqueous solution and water is (10-30): (10-60): (1-10): (0.1-1): (0:01-0.1): (10-30): (80-150); the concentration of the thickener aqueous solution is 3-5wt%.

[0014] Preferably, the particle size of the metal nitrate-loaded mesoporous carbon material is 0.8-1.2 μm; and the average particle size of the ceramic powder is 0.2-0.5 μm.

[0015] Preferably, the ceramic powder is selected from one or more of alumina, boehmite, calcium oxide or silicon dioxide; the binder is selected from polyacrylate binders or polyurethane binders; the dispersant is selected from one or more of polyacrylate ammonium salts, silane coupling agents, sodium hexametaphosphate, fatty alcohol polyoxyethylene ethers, fatty acid polyoxyethylene ethers or polyether modified polysiloxanes; the surfactant is selected from one or more of alkylphenol polyoxyethylene ethers, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate or octylphenol polyoxyethylene ether; the thickener is selected from sodium carboxymethyl cellulose or hydroxyethyl cellulose.

[0016] Preferably, in step S3, the coating thickness of the mixed slurry is 1-5 μm; and the drying temperature is 60-90°C.

[0017] In a second aspect, the present invention provides a lithium dendrite growth resistant composite diaphragm prepared by the above preparation method.

[0018] In a third aspect, the present invention provides a lithium-ion battery comprising: a lithium metal negative electrode, a positive electrode, an electrolyte and the above-mentioned anti-lithium dendrite growth composite diaphragm; a side of the anti-lithium dendrite growth composite diaphragm coated with a mixed slurry is in contact with the lithium metal negative electrode.

[0019] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0020] The present invention first uses metal nitrate to modify the mesoporous carbon material, and then mixes and coats the modified mesoporous carbon material with ceramic powder, wherein the dense accumulation of the ceramic powder plays a role in inhibiting the thermal shrinkage of the diaphragm substrate at high temperature and supporting the skeleton, and the rich porous structure of the mesoporous carbon material provides a large specific surface area, which is suitable for the loading and slow release of metal nitrate. During the operation of the battery, the metal nitrate on the diaphragm dissociates into metal ions and NO3 in the electrolyte. - The metal ions in the electrolyte with a higher redox potential than lithium will be reduced by the grown lithium dendrites, and the generated metal element will form an alloy SEI layer (solid electrolyte interface layer) with Li at the negative electrode interface, which plays a role in protecting the negative electrode. - It is beneficial to promote the rapid formation of conductivity and SEI layer, and the metal ions and NO3 in the composite membrane - It has the characteristic of continuous release, so it can continuously inhibit the growth of lithium dendrites. The addition of the above substances plays a synergistic role in protecting the negative electrode to improve the electrochemical and safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 These are disassembly pictures of failed battery cells of Example 1 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0023] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0024] The present invention provides a method for preparing a composite diaphragm for resisting lithium dendrite growth, comprising the following steps:

[0025] S1. preparing a metal nitrate-loaded mesoporous carbon material, wherein the metal nitrate has a metal redox potential higher than that of lithium;

[0026] S2, mixing the metal nitrate-loaded mesoporous carbon material, ceramic powder, binder, dispersant, surfactant and thickener aqueous solution in water to prepare a mixed slurry;

[0027] S3. Coat the mixed slurry on one side of the diaphragm substrate and dry it to obtain a composite diaphragm that resists lithium dendrite growth.

[0028] In the present invention, the pore size of the mesoporous carbon material is between 2 and 50 nm, which can effectively load metal nitrates. If mesoporous carbon is not added, the metal nitrates will block the pore structure of the diaphragm substrate, causing the permeability of the diaphragm to drop sharply, making it difficult to use in batteries. In addition, mesoporous carbon can also play a role in slow release of metal nitrates. The electrolyte in the pores of the mesoporous carbon material will dissociate the metal nitrates into metal ions and nitrate ions. Since the metal redox potential of the metal nitrate is higher than that of lithium, the metal ions will be reduced to metal elements by the grown lithium dendrites, thereby forming a lithium-metal alloy SEI layer, which effectively inhibits the growth of lithium dendrites. NO3 - This is conducive to promoting the rapid formation of the conductive and SEI layers. In the anti-lithium dendrite growth composite diaphragm of the present invention, the ceramic powder plays the role of supporting the skeleton, and its dense stacking effect can effectively play the role of thermal shrinkage of the diaphragm substrate at high temperatures. The above-mentioned substances work together to protect the negative electrode through synergistic effects to improve the electrochemical and safety performance of the battery.

[0029] In the present invention, the preparation method of the metal nitrate loaded mesoporous carbon material is as follows: the mesoporous carbon material is added into a metal nitrate aqueous solution, heated and stirred, then cooled and recrystallized, and filtered to obtain the mesoporous carbon material.

[0030] In the present invention, the mesoporous carbon material is selected from one or more of ordered mesoporous carbon CMK-3, nanoporous carbon NCP, porous activated carbon, porous carbon nanotubes, porous carbon fibers or porous carbon aerogels; the metal nitrate is selected from one or more of magnesium nitrate, calcium nitrate or potassium nitrate; the mass ratio of the mesoporous carbon material to the metal nitrate is 1:(1-5). If the amount of metal nitrate added is too little, it is difficult to effectively inhibit the growth of lithium dendrites. If the amount added is too much, it is difficult to effectively load. The present invention does not impose any special restrictions on the concentration of the metal nitrate aqueous solution, as long as the metal nitrate can be dissolved.

[0031] In the present invention, the temperature of the heating and stirring is 50-100°C, more preferably 60-80°C; the speed of the heating and stirring is 500-1000rpm, more preferably 600-800rpm; the time of the heating and stirring is 10-60min, more preferably 20-40min. The heating and stirring is to make the mesoporous carbon material and the metal nitrate aqueous solution fully mixed, so that the metal nitrate solution is evenly loaded inside the mesoporous carbon material.

[0032] In step S2 of the present invention, the mass ratio of the metal nitrate-loaded mesoporous carbon material, ceramic powder, binder, dispersant, surfactant, thickener aqueous solution and water is (10-30): (10-60): (1-10): (0.1-1): (0:01-0.1): (10-30): (80-150); the concentration of the thickener aqueous solution is 3-5wt%. The present invention does not impose any special restrictions on the order of adding and mixing each substance, and those skilled in the art can choose according to their needs, as long as a uniformly mixed mixed slurry can be prepared. The binder forms a firm bond between the solid part of the coating slurry and the diaphragm substrate; the dispersant reduces the adhesion between the solid particles in the slurry, promotes the uniform dispersion of the particles, and prevents the occurrence of agglomeration and precipitation; the surfactant prevents the solid particles from agglomerating, and the slurry foaming affects the coating effect, while improving the diaphragm wettability; the thickener is used to improve the rheology of the slurry and thicken to improve the stability of the slurry.

[0033] In the present invention, the particle size of the metal nitrate-loaded mesoporous carbon material is 0.8 to 1.2 μm; the average particle size of the ceramic powder is 0.2 to 0.5 μm. The ceramic powder with a smaller particle size is conducive to forming a dense stacking structure, thereby reducing the thermal shrinkage rate of the diaphragm substrate and improving the heat resistance of the composite diaphragm; but the ceramic powder with too small a particle size will greatly reduce the air permeability, thereby increasing the internal resistance of the battery, which is not conducive to the high-rate charge and discharge service of the battery. In the present invention, the particle sizes of the metal nitrate-loaded mesoporous carbon material and the ceramic powder are matched, so that the final composite diaphragm has suitable air permeability and good heat shrinkage resistance.

[0034] In the present invention, the ceramic powder is selected from one or more of alumina, boehmite, calcium oxide or silicon dioxide; the binder is selected from polyacrylate binders or polyurethane binders; the dispersant is selected from one or more of polyacrylate ammonium salt, silane coupling agent, sodium hexametaphosphate, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether or polyether modified polysiloxane; the surfactant is selected from one or more of alkylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate or octylphenol polyoxyethylene ether; the thickener is selected from sodium carboxymethyl cellulose or hydroxyethyl cellulose.

[0035] In the present invention, in step S3, the coating thickness of the mixed slurry is 1 to 5 μm, more preferably 2 to 3 μm; too thick a coating thickness will result in low air permeability, and too thin a coating thickness will result in poor air permeability. The present invention does not impose any special restrictions on the specific steps of coating, and a coating method commonly used in the art can be used. The drying temperature is 60 to 90°C, and the specific drying time depends on the drying conditions, and the present invention does not impose any special restrictions.

[0036] The present invention also provides a lithium dendrite growth resistant composite diaphragm prepared by the above-mentioned preparation method, which has good heat shrinkage resistance, air permeability and cycle stability. The longitudinal (MD) heat shrinkage rate and transverse (TD) heat shrinkage rate at 130°C are both lower than 1.5%, and the air permeability value is lower than 210s / 100cc, and the number of cycles reaches more than 2200.

[0037] The present invention also provides a lithium-ion battery, comprising: a lithium metal negative electrode, a positive electrode, an electrolyte and the above-mentioned anti-lithium dendrite growth composite diaphragm; the side of the anti-lithium dendrite growth composite diaphragm coated with the mixed slurry is in contact with the lithium metal negative electrode.

[0038] The present invention can use the lithium metal negative electrode, positive electrode and electrolyte commonly used by those skilled in the art for the lithium metal negative electrode, positive electrode and electrolyte, and the present invention will not be described in detail here.

[0039] The technical solution of the present invention is further described below in conjunction with specific embodiments. In the following embodiments, the base film used for coating is a polyethylene diaphragm. The pore size of the ordered mesoporous carbon CMK-3 is 10 nm and the particle size is 1 μm.

[0040] Example 1

[0041] This embodiment provides a method for preparing a composite diaphragm that resists lithium dendrite growth.

[0042] (1) Preparation of magnesium nitrate-loaded mesoporous carbon material: Deionized water was heated to 70°C, magnesium nitrate was added to prepare a magnesium nitrate solution, and ordered mesoporous carbon CMK-3 was added, and the mass ratio of deionized water, magnesium nitrate, and ordered mesoporous carbon was controlled to be 100:30:10; the solution was dispersed and stirred using a high-speed stirrer for 30 min at a speed of 700 r / min, and then the solution was cooled to room temperature for recrystallization and filtered to obtain the magnesium nitrate-loaded mesoporous carbon material.

[0043] (2) Preparation of mixed slurry: deionized water is added to sodium carboxymethyl cellulose powder, and a high-speed stirrer is used to mix and stir to obtain a sodium carboxymethyl cellulose solution. The stirring time is 60 minutes, and the mass ratio of sodium carboxymethyl cellulose to water is 3:70. Sodium hexametaphosphate dispersant is added to deionized water and stirred for 10 minutes, and then small-particle ceramic powder (Al2O3) with an average particle size of 0.3 μm is added and stirred for 180 minutes; then the magnesium nitrate-loaded mesoporous carbon material, polyacrylate binder and alkylphenol polyoxyethylene ether surfactant of step (1) are added in sequence and stirred for 45 minutes; finally, sodium carboxymethyl cellulose solution is added and stirred for 60 minutes to obtain a mixed slurry; in the mixed slurry, the mass ratio of metal nitrate-loaded mesoporous carbon material, small-particle ceramic powder, polyacrylate binder, sodium hexametaphosphate dispersant, alkylphenol polyoxyethylene ether surfactant, sodium carboxymethyl cellulose solution and water is 15:35:3:0.3:0.03:15:100.

[0044] (3) Preparation of composite diaphragm: The mixed slurry prepared in step (2) is coated on one side of the base film using a micro-gravure roller, and the coating thickness is controlled to be 2 μm. After coating, it is dried in an oven at 80° C.

[0045] Example 2

[0046] The difference between this embodiment and embodiment 1 is that the coating thickness in step (3) of this embodiment is controlled at 3 μm.

[0047] Example 3

[0048] The difference between this embodiment and embodiment 1 is that the dispersant in this embodiment is selected from ammonium polyacrylate, and the surfactant is selected from octylphenol polyoxyethylene ether.

[0049] Example 4

[0050] The difference between this embodiment and embodiment 1 is that magnesium nitrate is replaced by potassium nitrate in this embodiment.

[0051] Comparative Example 1

[0052] Compared with Example 1, this comparative example is different in that this comparative example does not contain magnesium nitrate, and the specific preparation steps are as follows:

[0053] (1) Preparation of mixed slurry: Deionized water was added to sodium carboxymethyl cellulose powder, and the mixture was mixed and stirred using a high-speed mixer to obtain a sodium carboxymethyl cellulose solution. The stirring time was 60 min, and the mass ratio of sodium carboxymethyl cellulose to water was 3:70. Sodium hexametaphosphate dispersant was added to deionized water and stirred for 10 min, and then small-particle ceramic powder (Al2O3) with an average particle size of 0.3 μm was added and stirred for 180 min; then ordered mesoporous carbon CMK-3, polyacrylate binder and alkylphenol polyoxyethylene ether surfactant were added in sequence and stirred for 45 min; finally, sodium carboxymethyl cellulose solution was added and stirred for 60 min to obtain a mixed slurry; in the mixed slurry, the mass ratio of ordered mesoporous carbon CMK-3, small-particle ceramic powder, polyacrylate binder, sodium hexametaphosphate dispersant, alkylphenol polyoxyethylene ether surfactant, sodium carboxymethyl cellulose solution and water was 15:35:3:0.3:0.03:15:100.

[0054] (2) Preparation of composite diaphragm: The mixed slurry prepared in step (1) is coated on one side of the base film using a micro-gravure roller, and the coating thickness is controlled to be 2 μm. After coating, it is dried in an oven at 80° C.

[0055] Comparative Example 2

[0056] The difference between this comparative example and Example 1 is that magnesium nitrate-loaded mesoporous carbon material is not added to the mixed slurry of this comparative example. The specific preparation steps are as follows:

[0057] (1) Preparation of mixed slurry: Deionized water was added to sodium carboxymethyl cellulose powder, and the mixture was mixed and stirred using a high-speed mixer to obtain a sodium carboxymethyl cellulose solution. The stirring time was 60 minutes, and the mass ratio of sodium carboxymethyl cellulose to water was 3:70. Sodium hexametaphosphate dispersant was added to deionized water and stirred for 10 minutes, and then small-particle ceramic powder (Al2O3) with an average particle size of 0.3 μm was added and stirred for 180 minutes; then polyacrylate binder and alkylphenol polyoxyethylene ether surfactant were added in sequence and stirred for 45 minutes; finally, sodium carboxymethyl cellulose solution was added and stirred for 60 minutes to obtain a mixed slurry; in the mixed slurry, the mass ratio of small-particle ceramic powder, polyacrylate binder, sodium hexametaphosphate dispersant, alkylphenol polyoxyethylene ether surfactant, sodium carboxymethyl cellulose solution and water was 35:3:0.3:0.03:15:100.

[0058] (2) Preparation of composite diaphragm: The mixed slurry prepared in step (1) is coated on one side of the base film using a micro-gravure roller, and the coating thickness is controlled to be 2 μm. After coating, it is dried in an oven at 80° C.

[0059] Comparative Example 3

[0060] The difference between this comparative example and Example 1 is that the average particle size of the ceramic powder in this comparative example is 0.8 μm.

[0061] Comparative Example 4

[0062] The difference between this comparative example and comparative example 3 is that this comparative example does not contain magnesium nitrate. The specific preparation steps are as follows:

[0063] (1) Preparation of mixed slurry: Deionized water was added to sodium carboxymethyl cellulose powder, and the mixture was mixed and stirred with a high-speed stirrer to obtain a sodium carboxymethyl cellulose solution. The stirring time was 60 min, and the mass ratio of the sodium carboxymethyl cellulose solution to water was 3:70. Sodium hexametaphosphate dispersant was added to deionized water and stirred for 10 min, and then small-particle ceramic powder (Al2O3) with an average particle size of 0.8 μm was added and stirred for 180 min; then ordered mesoporous carbon CMK-3, polyacrylate binder and alkylphenol polyoxyethylene ether surfactant were added in sequence and stirred for 45 min; finally, sodium carboxymethyl cellulose solution was added and stirred for 60 min to obtain a mixed slurry; in the mixed slurry, the mass ratio of ordered mesoporous carbon CMK-3, small-particle ceramic powder, polyacrylate binder, sodium hexametaphosphate dispersant, alkylphenol polyoxyethylene ether surfactant, sodium carboxymethyl cellulose solution and water was 15:35:3:0.3:0.03:15:100.

[0064] (2) Preparation of composite diaphragm: The mixed slurry prepared in step (1) is coated on one side of the base film using a micro-gravure roller, and the coating thickness is controlled to be 2 μm. After coating, it is dried in an oven at 80° C.

[0065] Test example

[0066] 1. Air permeability, thermal shrinkage and electrochemical cycle stability tests:

[0067] The coated diaphragm was tested for air permeability using a Wangyan EG01-55-1MR air permeability tester; the diaphragm was cut into a 10×10 cm pattern, and an A4 paper was placed on the top and bottom of the diaphragm and put into a vacuum oven. After baking at 130°C for 1 hour, the thermal shrinkage was measured.

[0068] Battery preparation: Lithium iron phosphate, binder PVDF, carbon nanotubes CNT, conductive agent SP and solvent NMP are stirred and slurried in a mass ratio of 96:2:1:1 for 6 hours, then coated on aluminum foil using a coating machine and dried, rolled and cut to prepare a positive electrode sheet. Graphite, aqueous binder, CNT, SP, CMC are stirred and mixed with the solvent in a mass ratio of 94:4:0.5:0.5:1, then the slurry is coated on copper foil and dried, rolled and cut to prepare a negative electrode sheet. The electrolyte is a mixture of EC (ethylene carbonate), PC (propylene carbonate), DEC (diethyl carbonate) and EMC (ethyl methyl carbonate) containing 1 mol / L LiPF6 (volume ratio 1:0.3:1:1). The above-mentioned positive electrode sheet, negative electrode sheet, and the composite diaphragms of Examples 1 to 2 and Comparative Examples 1 to 4 are made into soft-pack batteries. The 1C charge / discharge cycle test was performed using an electrochemical workstation and the test was stopped when the efficiency was lower than 80% SOC.

[0069] The test results of air permeability, thermal shrinkage and electrochemical cycle stability are shown in Table 1.

[0070] Table 1 Test results of air permeability, thermal shrinkage and electrochemical cycle stability

[0071]

[0072] From the comparison between Example 1 and Example 2, it can be seen that the increase in the thickness of the composite coating is conducive to improving the heat resistance and cycle life of the isolation membrane, but its permeability value will increase to a certain extent, indicating that the permeability has a certain decrease, but the permeability value is still lower than 210s / 100cc. From the comparison between Example 1 and Comparative Example 1, it can be seen that the mesoporous carbon material modified by magnesium nitrate is helpful to improve the cycle life of the battery and the service life of the battery cell. Figure 1 The pictures of disassembly of failed batteries in Example 1 and Comparative Example 1 show that the mesoporous carbon material modified with magnesium nitrate significantly improves the lithium precipitation phenomenon. From the comparison between Example 1 and Comparative Example 2, it can be seen that when magnesium nitrate is not added to load the mesoporous carbon material, the permeability value increases significantly, which is caused by the dense stacking of the ceramic powder, which will increase the internal resistance of the battery and is not conducive to the high-rate charge and discharge service of the battery; at the same time, the cycle performance of the battery decreases, indicating that the growth of lithium dendrites is not well suppressed. From the comparison between Example 1 and Comparative Example 3, it can be seen that when the particle size of the ceramic powder is too large, the stacking degree decreases, so the permeability value decreases, but the heat shrinkage resistance is significantly reduced, and the cycle stability is also reduced. When magnesium nitrate is not added to load the mesoporous carbon material on the basis of Comparative Example 3, the density of the composite diaphragm of Comparative Example 4 increases, so the permeability decreases and the heat shrinkage resistance is slightly improved. Due to the lack of the anti-lithium dendrite growth effect of the mesoporous carbon material loaded with magnesium nitrate, the cycle stability of the battery is significantly reduced.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite diaphragm that resists lithium dendrite growth, characterized in that: The steps include: S1. preparing a metal nitrate-loaded mesoporous carbon material, wherein the metal nitrate has a metal redox potential higher than that of lithium; S2, mixing the metal nitrate-loaded mesoporous carbon material, ceramic powder, binder, dispersant, surfactant and thickener aqueous solution in water to prepare a mixed slurry; S3. Coat the mixed slurry on one side of the diaphragm substrate and dry it to obtain a composite diaphragm that resists lithium dendrite growth.

2. The preparation method according to claim 1, characterized in that The preparation method of the metal nitrate loaded mesoporous carbon material is as follows: adding the mesoporous carbon material into a metal nitrate aqueous solution, heating and stirring, then cooling and recrystallizing, and filtering to obtain the material.

3. The preparation method according to claim 2, characterized in that: The mesoporous carbon material is selected from one or more of ordered mesoporous carbon CMK-3, nanoporous carbon NCP, porous activated carbon, porous carbon nanotubes, porous carbon fibers or porous carbon aerogels; the metal nitrate is selected from one or more of magnesium nitrate, calcium nitrate or potassium nitrate; the mass ratio of the mesoporous carbon material to the metal nitrate is 1:(1 to 5).

4. The preparation method according to claim 2, characterized in that: The temperature of the heating and stirring is 50-100° C., the speed of the heating and stirring is 500-1000 rpm, and the time of the heating and stirring is 10-60 min.

5. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the metal nitrate-loaded mesoporous carbon material, ceramic powder, binder, dispersant, surfactant, thickener aqueous solution and water is (10-30): (10-60): (1-10): (0.1-1): (0:01-0.1): (10-30): (80-150); the concentration of the thickener aqueous solution is 3-5wt%.

6. The preparation method according to claim 1, characterized in that: The particle size of the metal nitrate-loaded mesoporous carbon material is 0.8-1.2 μm; the average particle size of the ceramic powder is 0.2-0.5 μm.

7. The preparation method according to claim 1, characterized in that: The ceramic powder is selected from one or more of alumina, boehmite, calcium oxide or silicon dioxide; the binder is selected from polyacrylate binders or polyurethane binders; the dispersant is selected from one or more of polyacrylate ammonium salt, silane coupling agent, sodium hexametaphosphate, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether or polyether modified polysiloxane; the surfactant is selected from one or more of alkylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate or octylphenol polyoxyethylene ether; the thickener is selected from sodium carboxymethyl cellulose or hydroxyethyl cellulose.

8. The preparation method according to claim 1, characterized in that: In step S3, the coating thickness of the mixed slurry is 1-5 μm; and the drying temperature is 60-90°C.

9. A lithium dendrite growth resistant composite diaphragm prepared by the preparation method according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: include: A lithium metal negative electrode, a positive electrode, an electrolyte and the anti-lithium dendrite growth composite diaphragm according to claim 9; the side of the anti-lithium dendrite growth composite diaphragm coated with the mixed slurry is in contact with the lithium metal negative electrode.

Citation Information

Patent Citations

  • Anti-puncture diaphragm and application thereof in lithium battery

    CN114069156A

  • Heat-shrinkage-resistant and puncture-resistant polyolefin diaphragm material and preparation method thereof

    CN115863915A

  • Method for preparing lithium-sulfur battery modified diaphragm

    CN109950455A

  • Porous carbon loaded europium oxide material as well as preparation method and application thereof

    CN112688020A

  • High-wettability composite diaphragm as well as preparation method and application thereof

    CN118888975A